Neurocognitive processes of the religious leader in Christians - Ge, Jianqiao (Hum Brain Mapp, 2009)
Our recent work suggests that trait judgment of the self in Christians, relative to nonreligious subjects, is characterized by weakened neural coding of stimulus self‐relatedness in the ventral medial prefrontal cortex (VMPFC) but enhanced evaluative processes of self‐referential stimuli in the dorsal medial prefrontal cortex (DMPFC). The current study tested the hypothesis that Christian belief and practice produce a trait summary about the religious leader (Jesus) in the believers and thus episodic memory retrieval is involved to the minimum degree when making trait judgment of Jesus. Experiment 1 showed that to recall a specific incident to exemplify Jesus' trait facilitated behavioral performances associated with the following trait judgment of Jesus in nonreligious subjects but not in Christians. Experiment 2 showed that, for nonreligious subjects, trait judgments of both government and religious leaders resulted in enhanced functional connectivity between MPFC and posterior parietal cortex (PPC)/precuneus compared with self judgment. For Christian subjects, however, the functional connectivity between MPFC and PPC/precuneus differentiated between trait judgments of the government leader and the self but not between trait judgments of Jesus and the self. Our findings suggest that Christian belief and practice modulate the neurocognitive processes of the religious leader so that trait judgment of Jesus engages increased employment of semantic trait summary but decreased memory retrieval of behavioral episodes. Hum Brain Mapp, 2009. © 2009 Wiley‐Liss, Inc.